A sensitive and rapid method of lead detection using nanoparticle technology based on monoclonal antibody - Jia, Kunzhi; Lin, Ming; Zhao, Qiang; Dong, Mingke; Ling, Sumei; Wang, Shihua (Frontiers in Bioengineering and Biotechnology, 2022)
Lead (Pb) threatens public health due to its toxicity and non-biodegradable characteristic. It is of significance to develop a sensitive and rapid method for Pb detection. In this study, monoclonal antibodies against Pb were screened with an high affinity constant (Kaff) of 3.56×109 L/mol. Au nanosphere particles (AuNS) and Au nanoflower particles (AuNF) were synthesized with a diameter of 15 nm and 60 nm respectively. The specific anti-Pb antibodies were then immobilized on AuNS and AuNF for probes development. At last, AuNS- and AuNF-based strips were successfully assembled for comparative study, which were able to effectively detect environmental Pb in 10 min. The limits of detection (LOD) were determined to be 3.91 ng/mL and 0.2 ng/mL respectively. Thus the developed method provides a feasible solution for sensitive and rapid detection for Pb on site, which is beneficial to food safety and control of Pb contamination.